Cytomegalovirus Infection of the Rat Developing Brain In Utero Prominently Targets Immune Cells and Promotes Early Microglial Activation - Cloarec, Robin; Bauer, Sylvian; Luche, Herve; Buhler, Emmanuelle; Pallesi-Pocachard, Emilie; Salmi, Manal; Courtens, Sandra; Massacrier, Annick; Grenot, Pierre; Teissier, Natacha; Watrin, Francoise; Schaller, Fabienne; et al. (PLoS ONE, 2016)
Congenital cytomegalovirus infections are a leading cause of neurodevelopmental disorders in human and represent a major health care and socio-economical burden. In contrast with this medical importance, the pathophysiological events remain poorly known. Murine models of brain cytomegalovirus infection, mostly neonatal, have brought recent insights into the possible pathogenesis, with convergent evidence for the alteration and possible involvement of brain immune cells.In order to confirm and expand those findings, particularly concerning the early developmental stages following infection of the fetal brain, we have created a model of in utero cytomegalovirus infection in the developing rat brain. Rat cytomegalovirus was injected intraventricularly at embryonic day 15 (E15) and the brains analyzed at various stages until the first postnatal day, using a combination of gene expression analysis, immunohistochemistry and multicolor flow cytometry experiments.Rat cytomegalovirus infection was increasingly seen in various brain areas including the choroid plexi and the ventricular and subventricular areas and was prominently detected in CD45low/int, CD11b+ microglial cells, in CD45high, CD11b+ cells of the myeloid lineage including macrophages, and in CD45+, CD11b- lymphocytes and non-B non-T cells. In parallel, rat cytomegalovirus infection of the developing rat brain rapidly triggered a cascade of pathophysiological events comprising: chemokines upregulation, including CCL2-4, 7 and 12; infiltration by peripheral cells including B-cells and monocytes at E17 and P1, and T-cells at P1; and microglia activation at E17 and P1.In line with previous findings in neonatal murine models and in human specimen, our study further suggests that neuroimmune alterations might play critical roles in the early stages following cytomegalovirus infection of the brain in utero. Further studies are now needed to determine which role, whether favorable or detrimental, those putative double-edge swords events actually play.
EVALuna2:8313